LOCAL GOVERNMENT ROLE IN THE SOLVING OF CATCHING FISH ILLEGALLY IN ACEH REGION - Adwani Adwani; Mahfud Mahfud; Rosmawati Rosmawati (Faculty of Law, Universitas Jenderal Soedirman, 2016)
This study aimed to describe the shape of local government actions in tackling illegal fishing in Aceh, the handling of illegal fishing destructive fishery resources. The fundamental point is Law No. 45 Year 2009 concerning fisheries. This spesification of this research descriptive analysis, used both normative juridical approach and empirical. The results showed that the local government has made an effort preventive and repressive in the case of illegal fishing. To coordinate with relevant agencies and empower the role of traditional institutions of the sea to assist the role of government and law enforcement.Local governments should improve the coordination and supervision of the marine area, to monitor and evaluate the performance of local authorities in applying the law against this illegal fishing case.Keywords: Illegal, Local Government, and Fishing.